Lexical Collocations (Verb plus Noun) Across Written Academic Genres In English - Gulec, Nuray; Gulec, Bulent Arif (ELSEVIER SCIENCE BV, 2015)
The dominance of syntactic studies in linguistics has caused lexis and grammar to be perceived as two distinct categories. With introduction of the paradigm of cognitive linguistics, the studies in syntax have been replaced by those in lexis and concepts. Semantics has come to the fore through the studies in cognitive linguistics, and there has been a trend from syntactic studies to lexical ones. In addition to research in cognitive linguistics, construction grammar has also emphasized the continuum between lexis and grammar. With the emergence of corpus linguistics, the studies regarding the continuum between lexis and grammar have gained momentum, and thus studies of collocations have been theorized. Early studies of collocations have focused on only lexis and disregarded grammar. However, in the process the studies have also incorporated grammar as well, and this view supports the idea that each word has its own grammatical properties. Therefore, lexis and grammar should be studied on the same continuum because there is a continuum between these two categories rather than a discontinuum. Within the framework of this paradigm, this study focused on verb+noun lexical collocations across the health, physical and social sciences in the written academic genre and analyzed these lexical collocations through the frequency and chi-square analysis. The study aimed to search for commonalities and differences between the verbs with their collocations. The results showed that there were more similarities and relationship between the health and physical sciences, while the social sciences indicated a significant difference compared to the other two. The study found 165 common verbs used across the three sciences. 12 verbs among the 165 verbs were found to be candidates verb+noun lexical collocations as prototypes. (C) 2015 Published by Elsevier Ltd.
Keywords: Corpus linguistics; collocations; construction; prototype; written academic genre; Education & Educational Research; Social Sciences - Other Topics